Analisis Manajemen Proyek untuk Model Sistem Informasi Penjadwalan Pembelajaran pada SD X - Dewi Mustari; Tri Yani Akhirina; Theresia Evy Yulianty Nadeak (Politeknik Kampar, 2024)
Scheduling is a division of time so that the work is more efficient and orderly while learning is currently still done manually, so that it has several obstacles faced such as frequent clashes in learning schedules due to lack of accuracy when compiling learning schedules. The process without computerization will feel ineffective if there are many parameters and constraints used, the application of the scheduling information system that will be created later, will further improve performance in making schedules and processing scheduling data. This analysis will run according to plan and objectives, because Elementary School X will use this technology to improve teacher performance in compiling learning schedules. So the result of this analysis is that with the project management analysis for the scheduling information system model, we will be able to predict the needs of the system to be built.